Structural Design and Optimization of Flexible Commutation Amplification Mechanism based on Giant Magnetostrictive Actuator - Xu Bin Wang Chuanli Yu Caofeng Xie Tian (Jixie chuandong)
A micro-displacement transmission mechanism with giant magnetostrictive actuator (GMA) as the driving unit is designed, which uses lever-type flexure hinge for displacement commutation and amplification. Based on the theory of elasticity, the amplification ratio and natural frequency formulas of the flexible commutation amplification mechanism are derived by considering the deviation of the rotation center of the flexure hinge. The geometric parameters of the flexure hinge, such as radius R and minimum thickness t, are optimized and analyzed by using the software of Matlab, by which the optimized geometric parameters of the flexible hinge are obtained and the optimized results are analyzed by finite element analysis. Finally, the simulation results are compared with the theoretical analysis results. The results show that， the correctness of the theoretical model is verified by theoretical analysis and finite element analysis， and the design objective in high amplification ratio, displacement commutation and linear output is achieved.